1986
DOI: 10.1080/03015521.1986.10423072
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12and copper in blood serum and liver of hoggets in relation to cobalt and copper status of west coast South Island soils and pastures

Abstract: This study assessed the status of cobalt (Co) and copper (Cu) in yellow-brown earth (YBE) and pakihi soils, in pasture growing on these soils, and in serum and liver of lambs grazing for a year on the pasture. There had been no application of Co or Cu to YBE soils except in one instance, whereas these elements had been applied to pakihi soils at various times within the previous eight years since pasture establishment. Co in pasture was usually in the 'adequate' reference range category, although most of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…There were no significant liveweight gain responses to Se, Co or Cu measured. Later work on pakihi and terrace soils showed that initial application of cobalt and copper sulphate at sowing maintained blood serum and liver vitamin B 12 and Cu levels in the adequate range for up to 8 years (Morton 1986).…”
Section: Sheepmentioning
confidence: 99%
“…There were no significant liveweight gain responses to Se, Co or Cu measured. Later work on pakihi and terrace soils showed that initial application of cobalt and copper sulphate at sowing maintained blood serum and liver vitamin B 12 and Cu levels in the adequate range for up to 8 years (Morton 1986).…”
Section: Sheepmentioning
confidence: 99%